Catalogo delle concordanze musicali vivaldiane - Sardelli, Federico Maria (Florence Olschki, 2012)
A catalogue of Vivaldi's musical concordances, i.e., an inventory and synoptic view of all the musical loci communes in Vivaldi's oeuvre: from whole pieces down to small fragments, themes, phrases and musical ideas circulating within his vast opus and - sometimes - outside it, in composers from whom Vivaldi drew or who drew from Vivaldi. Its hundreds of cross-references and concordances of varying degrees draw a map of Vivaldi's language, his chronological evolution, and his creative and stylistic choices.The volume is divided into two parts: the Introduction, which lays the epistemological foundations of the concordance system, and the actual Catalog. A new tool is thus offered to tackle problems of dating and chronology, of attribution and identification, of the study of creative periods and of Vivaldi's compositional method. The author, responsible for the Ryom Catalog, updated the essay with the most recent catalog acquisitions.
Keywords: Vivaldi, Antonio -- 1678-1741; Catalog; Musicology